Early Christian remains of Inner Mongolia : discovery, reconstruction and appropriation - Halbertsma, Tjalling, 1969- (Sinica Leidensia, 2008)
The early Christian presence in Inner Mongolia forms the subject of this book. These Nestorian remains must primarily be attributed to the Ongut, a Turkic people closely allied to the Mongols. Writing in Syriac, Uighur and Chinese scripts and languages, the Nestorian Ongut drew upon a variety of religions and cultures to decorate their gravestones with crosses rising from lotus flowers, dragons and Taoist imagery. This heritage also portrays designs found in the Islamic world. Taking a closer look at the discovery of this material and its significance for the study of the early Church of the E.